PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI PENGARUH KEMAJUAN IPTEK TERHADAP NKRI - TRI SASTRI OKTIATI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
Student learning outcomes are the output of the teaching and learning process. One of the problems in learning at school is the low student learning outcomes. This can be seen from the initial data on students' daily test scores which are still below the KKM. Many factors influence learning outcomes, one of which is the learning model. The Problem Based Learning Learning Model is a cooperative learning model that requires students to be active and motivates students so that they can support and help each other in mastering the subject matter being studied. The research was conducted using the Problem Based Learning learning model. As for the statistical test using 2 cycles, the research results showed an increase in the percentage of preparation for learning activities from cycles 1 and 2 was 20.88%. For the average value of cycles 1 and 2, there was an increase of 5.15% with students who completed the study increasing from 22 people who completed their studies to 30 students who completed their studies with an increase of 13.6% from before. ABSTRAKHasil belajar siswa merupakan output dari proses belajar mengajar. Salah satu masalah dalam pembelajaran di sekolah adalah rendahnya hasil belajar siswa. Hal ini dapat diketahui dari data awal nilai ulangan harian siswa yang masih berada di bawah KKM. Banyak faktor-faktor yang mempengaruhi hasil belajar salah satunya adalah model pembelajaran. Model Pembelajaran Problem Based Learning merupakan model pembelajaran kooperatif yang menuntut siswa untuk aktif dan memotivasi siswa supaya dapat saling mendukung dan membantu satu sama lain dalam menguasi materi pelajaran yang dipelajari. Penelitian yang dilakukan menggunakan model pembelajaran Problem Based Learning. Adapun uji statistik menggunakan 2 siklus dihasilkan hasil penelitian Peningkatan prosentase persiapan aktivitas pembelajaran dari siklus 1 dan 2 adalah 20,88%. Untuk nilai rata-rata siklus 1 dan 2 mengalami kenaikan sebesar 5,15% dengan siswa yang tuntas meningkat dari 22 orang yang tuntas belajar menjadi 30 siswa yang tuntas dengan kenaikan 13,6% dari sebelumnya.